Alterações renais em pacientes com esquistossomose mansoni crônica em área de baixa endemicidade do Estado do Ceará : avaliação da função tubular e glomerular - Hanemann, Ana Lúcia de Paula (2012)
Renal involvement in schistosomiasis is rarely reported and can be characterized mainly by glomerular and may remain asymptomatic, hence the importance of biomarkers that can detect early changes in renal function. The objective was to characterize renal changes in patients with schistosomiasis mansoni before and after treatment in the intestinal phase, coming from an area of low endemicity in the state of Ceará. This is a cross-sectional study of character evaluation, quantitative and interventionist, including 85 patients with parasitological (Kato-Katz) confirmed schistosomiasis. Patients were divided into three groups: Group I (GI) - control group of 24 uninfected individuals, Group II (G-II) - a group of 30 individuals infected with S. mansoni and Group III (G-III) - group with 31 individuals infected with S. mansoni, processed and evaluated after treatment. Renal function was assessed by renal tubular and glomerular markers, including measurement of urinary pH, estimation of fractional excretion of electrolytes (FE), estimated glomerular filtration rate (eGFR), urinary albumin and urinary MCP-1/CCL2 ( Monocyte chemoattractant protein-1). Data from this study show that most subjects were within the age range around 23,2 ±13 years, 39 (45,88%) men and 46 (54,11%) women. When the renal tubular markers were analyzed it was found that there was no difference between groups. With respect to renal glomerular markers was observed that MCP-1 was the only one that was different, being higher in G-II (178 ± 97pg/mcg-Cr) and G-III (175 ± 87pg/mcg-Cr) when compared with the GI (123 ± 48pg/mcg-Cr), p = 0,009 and p = 0,007, respectively. There was no difference among the groups G-G-II and III (p = 0,892) were compared. Although the albumin excretion did not provide a difference between the three groups, it was correlated with MCP-1 (r= 0,463, p= 0.01). In short there was a significant increase in urinary levels of MCP-1 in patients with schistosomiasis. As this protein plays an important role in the recruitment of monocytes to sites of injury and infection, its increase in urine suggests that there is an inflammation of the kidneys and this is not reversed after treatment of this disease.